ANALISIS MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA MATERI LEMBAGA KEUANGAN DI SMA - Hafizin, Khairul; Ulfah, Maria; Basri, Muhammad (Universitas Tanjungpura, 2025)
This study aims to explore in depth the perceptions and experiences of teachers and tenth-grade students at SMA Negeri 1 Pemangkat regarding the use of Augmented Reality (AR)-based learning media in financial institution material. The background of this study stems from the continued dominance of conventional approaches in the teaching and learning process, which are considered less capable of bridging abstract concepts and motivating students optimally. Using a qualitative method with a case study design, data collection was conducted through in-depth interviews and participatory observation of economics teachers and 31 students. The analysis process was conducted thematically and interpreted using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) and Self-Determination Theory (SDT) frameworks. The research findings indicate that the use of AR media has a positive impact on students' performance expectations and hedonic motivation, while also strengthening the fulfillment of their psychological needs related to competence and autonomy. However, factors such as facility support and social influence remain key aspects influencing the acceptance of this technology. This article presents in-depth qualitative findings on the opportunities and challenges in implementing AR, and offers practical recommendations for the development of more effective and contextual technology-based learning media in the future.